Module 12: Local institutions - Kristjanson, Patricia M.; Gordes, A.; Sessa, R.; Braimoh, A.K.; Vermeulen, Sonja J. (Food and Agriculture Organization of the United Nations, 2013)
Improving smallholder agricultural systems is central to achieving climate-smart agriculture (CSA). This module focuses on local-level institutions and their role in facilitating the adoption of climate-smart agricultural strategies. The module demonstrates the importance of local institutions for CSA projects (Section 12.1); outlines priorities, needs, similarities and differences between key institutions (Section 12.2); and discusses considerations to bear in mind when building inter-institutional synergies for CSA initiatives (Section 12.3). Finally, it offers basic, practical guidelines to help practitioners and policy-makers build institutional support for CSA (Section 12.4).